Spatial Estimation of Finite Population Total under Geographically Weighted Regression using Forward Stepwise Variable Selection - Nobin Chandra Paul; Anil Rai; Tauqueer Ahmad; Ankur Biswas; Prachi Misra Sahoo (Journal of the Indian Society of Agricultural Statistics, 2024)
Unlike ordinary least square model, the geographically weighted regression model takes into account spatial non-stationarity and can capture the spatially varying relationship between several variables. Although, a particular model should contain all pertinent covariates but too many insignificant covariates make the model unnecessarily complex. Therefore, it is important to choose important covariates having significantly high correlation with the study variable. Here, a forward stepwise variable selection procedure under the geographically weighted regression model framework has been proposed for choosing significant covariates and compared with the existing forward stepwise ordinary least square method. Further, an estimator of finite population total incorporating spatial information has been developed. The performance of the proposed spatial estimator was compared empirically under both forward stepwise geographically weighted regression and forward stepwise ordinary least square method through a spatial simulation study. It was found that the performance of the spatial estimator using forward stepwise geographically weighted regression method is better than the forward stepwise ordinary least square method.